PERFORMANCE KELINCI YANG DIBERI BERBAGAI PROBIOTIK DALAM AIR MINUM - Herlina, Betty; judolaksono, Judo laksono; Riyadi, Reza (Universitas Muara Bungo, 2024)
ABSTRACTThis study aims to determine the effect of adding various probiotics in drinking water to the performance of rabbits. The research was carried out from 15 December 2022 to 13 January 2023 at the Green Garden Housing District, Lubuklinggau Barat I District, Lubuklinggau City. This study used an experimental method with a Completely Randomized Design (CRD) Non Factorial consisting of 6 treatments and 4 replications, so there were 24 treatment combinations. The arrangement of the treatments that will be carried out in this study are as follows: P0: Drinking water without probiotics P1: Drinking water added with Yoghurt 1 ml/500 ml water P2: Drinking water added with Yakult 1 ml/500 ml water P3: Drinking water added with Viterna Plus 1 ml/500 ml water P4 : Biobig drinking water added 1 ml/500 ml water P5 : Drinking water added EM4 Animal Husbandry 1 ml/500 ml water. Parameters observed were feed consumption, body weight gain, feed conversion, mortality, and drinking water consumption. This research uses ANOVA analysis and BNJ follow-up test. The results of this study showed that the addition of various probiotics in drinking water had a very significant effect (P0.01) on feed consumption, body weight gain and feed conversion, while it had no significant effect (P0.05) on drinking water consumption. This study concluded that the P4 (Biobig) treatment gave the best results in feed consumption and body weight gain. Because Biobig contains turmeric extract which can increase rabbit feed consumption so this can also increase body weight gain in rabbits.